Peran Pembelajaran Pendidikan Kewarganegaraan di Lingkungan Sekolah dalam Membentuk Karakter Siswa yang Berakhlak, Berwawasan Kebangsaan dan Cinta Tanah Air - Irpan Irpan; Syamzaimar Syamzaimar (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Civic Education holds a strategic position within the national education system as the primary instrument for shaping the personality of citizens in alignment with the values of Pancasila. This research is motivated by the phenomenon of moral degradation and the fading spirit of nationalism among the younger generation due to the unfiltered influence of globalization. The primary objective of this study is to analyze the extent of Civic Education's role in the school environment in transforming student character to possess noble morals, broad national insight, and a deep love for the motherland. The research method employed is a literature study with a qualitative approach, where data were collected through the analysis of various curriculum documents, scientific journals, and textbooks relevant to the implementation of the independent curriculum. Research findings indicate that Civic Education is not merely a theoretical transfer of civic knowledge but rather an effective process of value internalization through behavioral habituation within the school environment. The integration of teaching materials with practical applications in school life is proven to increase students' awareness of their rights and obligations as citizens. The analysis also reveals that strengthening moral character and national insight highly depends on teacher creativity in delivering interactive learning that is relevant to the students' social reality. The implications of this research emphasize the importance of revitalizing Civic Education teaching methods to be more adaptive to modern developments without losing national identity. Schools are expected to serve as laboratories of democracy and centers for sowing patriotic values to produce a golden generation that is not only intellectually competent but also possesses strong moral integrity to maintain the integrity of the Republic of Indonesia.